1961
DOI: 10.1103/physrev.122.1754
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Temperature Dependence of Young's Modulus for Several Oxides

Abstract: Young's modulus was measured over the temperature range 77°-850°K by an accurate resonance technique. Data are presented for single crystals of aluminum oxide with various orientations of the crystallographic axes and for polycrystalline aluminum oxide, thorium oxide, and magnesium oxide. The results show that the range of validity of a T 4 temperature dependence predicted by theory must be quite small. The temperature dependence is very well described over the whole temperature range by T exp(-T 0 /T), where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
168
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(191 citation statements)
references
References 10 publications
14
168
1
Order By: Relevance
“…The derivative with respect to temperature of any elastic constant tends towards zero approaching absolute zero [128], while a linear dependence of Young's modulus with respect to temperature has been observed for many crystalline solids at high temperatures [128]. A simple linear fit has been used by several researchers for the temperature dependence of elastic moduli, as the deviation from linear variation with temperature is small except at low temperatures [129].…”
Section: Young's Bulk and Shear Modulimentioning
confidence: 99%
See 1 more Smart Citation
“…The derivative with respect to temperature of any elastic constant tends towards zero approaching absolute zero [128], while a linear dependence of Young's modulus with respect to temperature has been observed for many crystalline solids at high temperatures [128]. A simple linear fit has been used by several researchers for the temperature dependence of elastic moduli, as the deviation from linear variation with temperature is small except at low temperatures [129].…”
Section: Young's Bulk and Shear Modulimentioning
confidence: 99%
“…However, this fit can lead to a slight over-estimation of the room temperature Young's modulus from intermediate or high temperature data. The Wachtman equation has been shown to accurately describe the temperature dependence of Young's modulusprovided the variation in Poisson's ratio with temperature is small-or bulk modulus, across a broad range of temperature for various non-metallic crystals and polycrystalline ceramics [128,130]:…”
Section: Young's Bulk and Shear Modulimentioning
confidence: 99%
“…However, since the elastic modulus of the individual phases are not available at elevated temperatures, the effective modulus is used here. The results of measurement and data from Fukuhara and Sanpei (1993) are plotted in figure 3 along with the model by Wachtman et al (1961) …”
Section: Coupling Of Phase and Flow Stress Modelsmentioning
confidence: 99%
“…13 The third law of thermodynamics requires that the derivative of any elastic constant with respect to the temperature must approach zero as the temperature approaches absolute zero. Combining this criterion with the observed linear relationship at higher temperatures, Wachtman et al 14 where B 0 is the bulk modulus at absolute zero, T is the temperature, and b 1 and T 0 are arbitrary constants. Theoretical justification for the equation of Wachtman et al was suggested by Anderson.…”
Section: Introductionmentioning
confidence: 99%